2005
DOI: 10.1038/ng1591
|View full text |Cite
|
Sign up to set email alerts
|

Dynein mutations impair autophagic clearance of aggregate-prone proteins

Abstract: Mutations that affect the dynein motor machinery are sufficient to cause motor neuron disease. It is not known why there are aggregates or inclusions in affected tissues in mice with such mutations and in most forms of human motor neuron disease. Here we identify a new mechanism of inclusion formation by showing that decreased dynein function impairs autophagic clearance of aggregate-prone proteins. We show that mutations of the dynein machinery enhanced the toxicity of the mutation that causes Huntington dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
328
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(342 citation statements)
references
References 30 publications
12
328
0
2
Order By: Relevance
“…3,67 Dynein inhibition by EHNA suppressed fusion of autophagosomes and lysosomes. 68 Dynactin 1, a member of the Dynactin complex, which is essential for dynein function in motility was also linked to autophagosomal transport. 69 RINT1 and Dynactin1 interact with ZW10 in a competitive manner 70 and it was suggested that the RINT1/ZW10 complex may play as an ER anchor for the Dynein-Dynactin complex carried vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…3,67 Dynein inhibition by EHNA suppressed fusion of autophagosomes and lysosomes. 68 Dynactin 1, a member of the Dynactin complex, which is essential for dynein function in motility was also linked to autophagosomal transport. 69 RINT1 and Dynactin1 interact with ZW10 in a competitive manner 70 and it was suggested that the RINT1/ZW10 complex may play as an ER anchor for the Dynein-Dynactin complex carried vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagosomes move bidirectionally along microtubules. Their centripetal movement is dependent on the dynein motor [80,81]. Two types of fusion have been documented [77]: 1, complete fusion of the autophagosome with the lysosome; 2, transfer of material from the autophagosome to the lysosomal compartment following a kiss-and-run fusion process in which two separate vesicles are maintained [49].…”
Section: Microtubules Destabilization Of Microtubules By Eithermentioning
confidence: 99%
“…It is now conceivable that changes in the enzymes of this complex could partially underlie autophagic dysfunction in neurodegenerative diseases [13] . In addition to defects in the induction process, genetic or functional alterations may occur in the autophagosome maturation, autolysosome formation, or autophagosome clearance processes [14] . For example, when components of the dynein motor machinery, such as dynein, dynactin or tubulin deacetylases, undergo changes, autophagosome-lysosome fusion is impaired, leading to decreased autophagic clearance of protein aggregates and enhanced neurotoxicity in animal models of HD and ALS [15][16][17] .…”
Section: Autophagic Flux Defects In Neurodegenerative Diseasesmentioning
confidence: 99%